Comparative study on the combustion and gasification of solid recovered fuels. Emphasis on residues characterisation and chlorine partitioning - Balampanis, Dimitris E. (Cranfield University, 2009)
Thermal treatment is recognised as a valid option within the waste management hierarchy for the recovery of the energy content of waste. Recent developments in the field are signposted from emergent technologies and the standardisation of solid recovered fuels. This work comparatively examines the fluidized bed combustion and gasification of a novel material; East London’s solid recovered fuel. Emphasis is given on the characterisation of the solid residues produced from the two thermal treatment techniques and chlorine partitioning, in particular. Chlorine mass balances are studied under steady state conditions for combustion and gasification. Furthermore, trace metals content, chlorobenzenes, major elements, crystalline structures, and leaching behaviours are compared in the two residues types. For the characterisation of these residues a series of analytical methods have been applied and compared for their efficiencies. Results indicate that gasification produces 5-6 times less HCI than combustion. Furthermore, gasification residues retain higher amounts of CI and in less water soluble forms. However, gasification residues have 3-8 times higher organochlorides load, expressed chlorobenzenes. This work generates novel data on the comparative characterisation of waste thermal treatment residues. These data contribute towards the technical confidence for further utilisation of solid recovered fuels, and the knowledge over the residues’ properties.